Vitamin D Status and Its Associated Risk Factors among Adults in the Southwest Region of Cameroon. (19th March 2018) - Tangoh, Delphine A.; Apinjoh, Tobias O.; Mahmood, Yasir; Nyingchu, Robert V.; Tangunyi, Beatrice A.; Nji, Emmanuel N.; Azhar, Abid; Achidi, Eric A.
Abstract : Background . Vitamin D has been shown to exert its actions on the musculoskeletal, gastrointestinal, prostate, renal, endocrine, immune, and cardiovascular systems. Current reported data of hypovitaminosis D reveals a global pandemic, with an estimated one billion people worldwide presenting with hypovitaminosis D. Objective . This study aimed at investigating the vitamin D status and its associated risk factors in Cameroonians from the South West Region. Method . The study was a community- and hospital-based prospective longitudinal study. It was carried out during the dry and rainy seasons between the months of July and December 2015 in the South West Region of Cameroon involving 372 participants aged 35 years and above. After obtaining informed consent, a structured questionnaire was used to capture demographic data and risk factors of vitamin D deficiency. Blood samples were collected from the volunteer participants in the peak months of the rainy season and dry season, and the serum used to analyse for vitamin D by ELISA and calcium by spectrophotometry. 25(OH)D levels ≥75 nmol/L (≥30 ng/mL) were considered sufficient while levels <75 nmol/L were considered as hypovitaminosis D (insufficiency/deficiency). Results . Hypovitaminosis D (deficiency/insufficiency) was prevalent in 25.8% (96) of the study population, with only 3.2% (12) deficiency and 22.6% (84) insufficiency. There was a significant inverse relationshipr = − 0.119, p = 0.02 between age and 25(OH)D levels; however, this relationship was not significant when controlled for gender, number of hours spent outdoors, and percentage of body covered. Gender, ethnic origin, percentage of body covered, time spent outdoors, and season did not influence serum vitamin D levels. Conclusion . Results of this study suggest that the prevalence of hypovitaminosis D is relatively low in this study population and only age is a risk factor of vitamin D deficiency.